2018
DOI: 10.2147/opth.s140411
|View full text |Cite
|
Sign up to set email alerts
|

Impact of virtual reality simulation on learning barriers of phacoemulsification perceived by residents

Abstract: ObjectiveTo identify residents’ perceived barriers to learning phacoemulsification surgical procedures and to evaluate whether virtual reality simulation training changed these perceptions.DesignThe ophthalmology residents undertook a simulation phacoemulsification course and proficiency assessment on the Eyesi system using the previously validated training modules of intracapsular navigation, anti-tremor, capsulorrhexis, and cracking/chopping. A cross-sectional, multicenter survey on the perceived difficultie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
0
15
0
3
Order By: Relevance
“…McCannel et al 15 presented that VR simulation could reduce the rate of errant capsulorhexis. Ng et al 16 reported that residents who had completed the VR training had greater confidence in performing phacoemulsification. In addition to surgical training, Wilson et al 8 reported that the VR ophthalmoscope training could successfully simulate performing eye examinations.…”
Section: Discussionmentioning
confidence: 99%
“…McCannel et al 15 presented that VR simulation could reduce the rate of errant capsulorhexis. Ng et al 16 reported that residents who had completed the VR training had greater confidence in performing phacoemulsification. In addition to surgical training, Wilson et al 8 reported that the VR ophthalmoscope training could successfully simulate performing eye examinations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the virtual reality cataract surgical simulator Eyesi (VRmagic, Mannheim, Germany) has also shown improved performance among cataract surgery trainees [ 27 ]. Eyesi cataract simulation training has shown improvements in resident ophthalmologists’ confidence in performing phacoemulsification [ 28 ]. A Royal College of Ophthalmologists’ National Ophthalmology database study of nearly 18,000 cases performed by first- and second-year residents showed a 38% reduction in posterior capsule rupture rates for residents who’d undergone simulation training compared to trainees who did not receive this form of simulation training [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…La adición del entrenamiento de simulación quirúrgica se asoció con una tasa significativamente reducida de complicaciones, incluyendo desgarros de la cápsula posterior y prolapso vítreo Siu-Chung et al 2018 21 Estudio prospectivo, transversal, multicéntrico (ICO-OSCAR) Eyesi Catarata…”
Section: Evaluación De La Validez De Constructo En El Uso De Simulaciunclassified
“…Siu-Chung y colaboradores descubrieron que aquellos residentes que se entrenaron con realidad virtual y que completaron el entrenamiento de simulación Eyesi tenían mayor confianza en la realización de las tareas más difíciles durante la facoemulsificación. 21 PhacoVision es un simulador de realidad virtual para la técnica de cirugía de cataratas usando facoemulsificación. Algunos de los estudios realizados para este simulador destacan el desarrollo de índices integrados para monitorear el desempeño de los usuarios durante el entrenamiento en cirugía de cataratas.…”
Section: Residentesunclassified